A Low Ankle-Brachial Index and High Brachial-Ankle Pulse Wave Velocity Are Associated with Poor Cognitive Function in Patients Undergoing Hemodialysis. (19th August 2019) - Wu, Ping-Hsun; Lin, Yi-Ting; Wu, Pei-Yu; Huang, Jiun-Chi; Chen, Szu-Chia; Chang, Jer-Ming; Chen, Hung-Chun
Abstract : Patients with end-stage renal disease (ESRD) have an increased risk of both impaired cognitive function and peripheral artery disease (PAD) than the general population. The association between PAD and dementia is recognized, but there are limited studies in patients with ESRD. The aim of this study was to evaluate the relationship between ankle-brachial index (ABI) and brachial-ankle pulse wave velocity (baPWV) and cognitive impairment in patients receiving hemodialysis (HD). We enrolled 136 prevalent HD patients (mean age59.3 ± 10.5 years, 55.9% male). Cognitive performance was measured using the Montreal Cognitive Assessment (MoCA) and Cognitive Abilities Screening Instrument (CASI) by trained psychiatrists. Associations between the cognitive function and ABI and baPWV were assessed using multiple linear regression analysis. Compared with HD patients withABI ≥ 0.9, patients withABI < 0.9 had lower MoCA score (p = 0.027 ) and lower CASI score but did not achieve significant level (p = 0.056 ). In the multivariate stepwise linear regression analysis, ABI (per 0.1) was independently positively associated with the MoCA score (β   coefficient = 0.62, p = 0.011 ) and the CASI score (β   coefficient = 1.43, p = 0.026 ). There is a negative association between baPWV (per 100 cm/s) and CASI (β   coefficient = − 0.70, p = 0.009 ). In conclusion, a low ABI or high baPWV was associated with a lower cognitive function in HD patients.